2011
DOI: 10.13182/fst11-a11578
|View full text |Cite
|
Sign up to set email alerts
|

Subterahertz Emission at Strong REB-Plasma Interaction in Multimirror Trap GOL-3

Abstract: Investigation results for electromagnetic radiation emission induced by strong Langmuir turbulence driven by a microsecond relativistic electron beam are presented. The radiation is associated with a plasmonplasmon merging process, which generates photons at a double plasma frequency in the range of few hundredsGHz. An original radiometric system for radiation spectrum and power measurements is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…A plasma column had a diameter about of 8 cm and a length about of 14 m. In the first series of the experiments carried out for the plasma density of a few units of 10 14 cm -3 , it was found that emitted pulses of mm-waves and sub-terahertz radiation by the beamplasma system continued 1-3 µs from the beam injection beginning, as a rule, and the most part of the emission was concentrated in the first two meters of the beam way along the plasma column [3].…”
Section: Key Results Of Gol-3 Experimentsmentioning
confidence: 98%
See 2 more Smart Citations
“…A plasma column had a diameter about of 8 cm and a length about of 14 m. In the first series of the experiments carried out for the plasma density of a few units of 10 14 cm -3 , it was found that emitted pulses of mm-waves and sub-terahertz radiation by the beamplasma system continued 1-3 µs from the beam injection beginning, as a rule, and the most part of the emission was concentrated in the first two meters of the beam way along the plasma column [3].…”
Section: Key Results Of Gol-3 Experimentsmentioning
confidence: 98%
“…To verify astrophysical models of various mechanisms of the EM-wave generation in space plasma, supporting laboratory beam-plasma experiments are carried out. From other hand, such beam-plasma systems are very attractive for the development of generators of radiation in millimeter and submillimeter ranges [3,4]. Motivated by these circumstances, we study the systems in laboratory experiments since 70-th of the past century [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discharge plasma current stabilizes simultaneously the beam injection process. Previous experiments have shown that the variation of the power value of the emitted electromagnetic waves correlates with the changes in the efficiency of plasma heating by the electron beam and the both wave generation and plasma heating processes lasts during the first half of the injection time [1][2][3][4][5]. It was decided therefore to maximize the number of diagnostics at the first meter of the plasma column (see.…”
Section: The Experimental Devicementioning
confidence: 99%
“…In view of these circumstances, we turned to the task on the generation of sub-terahertz radiation due to intense interaction of a high-current electron beam with plasma. Generation of powerful electromagnetic radiation in this frequency area under collective deceleration of highcurrent electron beam in plasma column was experimentally and theoretically studied at the Budker Institute of Nuclear Physics during last five years [1][2][3][4][5]. This generation is interpreted as result of high level power density of longitudinal (Langmuir) and/or oblique (upper-hybrid) waves excited by the strong electron beam.…”
Section: Introductionmentioning
confidence: 99%